Book reviews.
The Qualtiy Toolkit : An A-Z of Tools and Techniques, by John Marsh. Reviewed by John Bessant (Brighton, UK)
Bringing Technology Home : Gender and Technology in a Changing Europe, edited by Cynthia Cockburn and Ruza Furst Dilic. Reviewed by Gillian Shapiro (Brighton, UK)